IMPROVING THE COST AUDIT IN THE PUBLIC SECTOR OF UZBEKISTAN - Yariev Sherzod (Modern American Journals, 2025)
The article discusses the features of improving the cost audit in the public sector in the Republic of Uzbekistan and theoretical issues of using international experience.
Keywords: Financial control, cost audit, audit in the public sector, audit standards, expenditures.